The role of brahmins in the sinhalese monarchy: a Study based on the kingdom of Anuradhapura - Aniththa, S. (Rajarata University of Sri Lanka, 2023)
The Kingdom of Anuradhapura founded by King Pandukabhaya in 377 BC, was the first important kingdom in the political, economic and cultural history of Sri Lanka until the Chola invasion in 993 AD. When Buddhism spread to Sri Lanka in the 3rd century BC, many people and kings adopted Buddhism as their religion and it developed into a state-supported religion. Thus, Buddhism and Buddhist priests had influence on the Sinhalese kings and Anuradhapura kingdom is prioritized as a Buddhist kingdom in the Pali literature and by the late historians. However, there are evidences that the Sinhalese dynasty worshiped Hindu gods during this period, many Sinhalese kings built many Hindu temples, supported Hindu religion by participating in Hindu worship, festivals, activities, etc. Thus, the objective of this research is to highlight the role of Brahmins who learned the Vedas and Shastras in the Sinhalese monarchy during the kingdom of Anuradhapura with the help of Pali, Sinhalese literature and inscriptions. Pali, Sinhala literature and inscriptions are the primary sources of this research and the books, research articles and website articles of the scholars who have conducted research on the Anuradhapura period culture, the origin and development of Hinduism in Sri Lanka have been used as secondary evidence. The research has been done with a historical approach using analytical, descriptive and explanatory methods to achieve the objective of this research. Although Buddhism and Buddhist priests had influence on the Anuradhapura government, the Brahmins served in many levels as priests, Rajaguru, ambassadors, physicians, close friends and advisers of kings, military commanders and ministers worthy of the trust and honor of the king and performers of rituals, ceremonies and functions in the monarchy of the Sinhalese kings. Thus, due to their close relationship with the royal family, the marriage relationship arose and a Brahmin being appointed as the king by the Sinhalese queen in Anuradhapura politics. These evidence highlights the position of Brahmins in the Anuradhapura Sinhalese monarchy and the support given by the Sinhalese kings to the Brahmins and Hinduism. Through these, it can be said that during the period of the Anuradhapura kingdom, Hinduism and Buddhism had developed in Sri Lanka in the absence of religious differences between the Tamil and Sinhalese people.
Keywords: Hinduism; Brahmins; Anuradhapura; Sinhala Kings